2019
DOI: 10.3389/fncel.2019.00037
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modulation of Human α7 Nicotinic Receptor by Amyloid-β Peptides

Abstract: Amyloid β peptide (Aβ) is a key player in the development of Alzheimer’s disease (AD). It is the primary component of senile plaques in AD patients and is also found in soluble forms. Cholinergic activity mediated by α7 nicotinic receptors has been shown to be affected by Aβ soluble forms. To shed light into the molecular mechanism of this effect, we explored the direct actions of oligomeric Aβ1–40 and Aβ1–42 on human α7 by fluorescence spectroscopy and single-channel recordings. Fluorescence measurements usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
46
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 84 publications
11
46
2
Order By: Relevance
“…We found that the PSEN1 E280A ChLN response to ACh was significantly reduced by day 4 post transdifferentiation. Notably, Aβ has been shown to directly affect α7 nicotinic ACh receptor (α7 nAChR) function by acting as an agonist (~100 nM) and a negative modulator (at high concentrations) [71]. Consistent with this view, we confirmed that PSEN1 E280A ChLNs secreted aberrant amounts of Aβ42 (e.g.,~2500-f.i.)…”
Section: Plos Onesupporting
confidence: 82%
“…We found that the PSEN1 E280A ChLN response to ACh was significantly reduced by day 4 post transdifferentiation. Notably, Aβ has been shown to directly affect α7 nicotinic ACh receptor (α7 nAChR) function by acting as an agonist (~100 nM) and a negative modulator (at high concentrations) [71]. Consistent with this view, we confirmed that PSEN1 E280A ChLNs secreted aberrant amounts of Aβ42 (e.g.,~2500-f.i.)…”
Section: Plos Onesupporting
confidence: 82%
“…We found that the PSEN1 E280A ChLN response to ACh was significantly reduced by day 4 post transdifferentiation. Notably, A has been shown to directly affect 7 nicotinic ACh receptor (7 nAChR) function by acting as an agonist (~100 nM) and a negative modulator (at high concentrations) [71]. Consistent with this view, we confirmed that PSEN1 E280A…”
Section: Discussionsupporting
confidence: 83%
“…Consistently, A␤ binds different targets in a concentration-dependent manner (Mura et al, 2012;Zappettini et al, 2012). and, recently, it has been shown that A␤ directly affects ␣7-nAchR conformation and function by acting as an agonist when at picomolar concentrations or as an antagonist when at nanomolar concentrations (Lasala et al, 2019). It should be also considered that at high A␤ concentrations, the amount of oligomerization proportionally increases overrunning the physiological level (Gulisano et al, 2018a,b).…”
Section: Discussionmentioning
confidence: 94%